Splay-foot in cattle - R.R. Schalles; R.W. Markham; H.W. Leipold; M.F. Spire (Kansas Agricultural Experiment Station Research Reports, 1989)
Angular limb deformity, observed in several breeds of cattle, results in a knock-kneed and splay-footed condition in the front legs. This study shows that angular limb deformity is a congenital structural defect, inherited as a simple, autosomal, recessive trait.
Keywords: Cattlemen' s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; https://krex.k-state.edu/dspace/handle/2097/6456